TEACHING FOREIGN LANGUAGES IN MIXED-LEVEL GROUPS: CHALLENGES AND PRACTICAL METHODOLOGICAL SOLUTIONS (Web of Teachers: Inderscience Research, 2026)
Teaching foreign languages in mixed-level groups is a common reality in many educational settings. In one classroom, teachers often work with learners who differ in language proficiency, learning pace, motivation, confidence, background knowledge, and communicative ability. Such diversity creates both challenges and opportunities. Lower-level learners may feel anxious or discouraged, while more advanced students may lose interest if the lesson does not challenge them enough. For this reason, traditional one-size-fits-all teaching is often ineffective in mixed-level language classrooms. This article discusses the main challenges of teaching foreign languages in mixed-level groups and offers practical methodological solutions based on modern educational research. It draws on differentiated instruction, sociocultural theory, scaffolding, task-based language teaching, flexible grouping, peer learning, formative assessment, feedback, and technology-supported learning. The article argues that mixed-level classrooms should not be treated only as a difficulty, but also as a productive space where learner diversity can be used as a resource for more inclusive and effective language teaching.